An Unusual Cause of Transient Ischemic Attack in a Patient with Pacemaker - Jagadeesh Kumar Kalavakunta; Vishal Gupta; Basil Paulus; William Lapenna (Case Reports in Cardiology)
Pacemaker lead malposition in various locations has been described in the literature. Lead malposition in left ventricle is a rare and an underdiagnosed complication. We present a 77-year-old man with history of atrial fibrillation and pacemaker placement who was admitted for transient ischemic attack. He was on aspirin, beta blocker, and warfarin with subtherapeutic international normalized ratio. His paced electrocardiogram showed right bundle-branch block, rather than the typical pattern of left bundle-branch block, suggesting pacemaker lead malposition. Further, his chest X-ray and echocardiogram confirmed the pacemaker lead position in the left ventricle instead of right ventricle. He refused surgical removal of the lead and we increased his warfarin dose. Diagnosis of lead malposition in left ventricle, though easy to identify in echocardiogram, requires high index of clinical suspicion. In asymptomatic patients, surgical removal may be deferred for treatment with lifelong anticoagulation.